On the jury trial: principles and practices for effective advocacy - Melsheimer, Thomas M. (UNT Press, 2017)
Voir dire -- Opening statement -- Preparing witnesses: direct examination and cross examination -- Cross examination -- Expert witness -- Using demonstrative exhibits and other aids -- Closing argument -- Court's charge -- Jury research -- Motions in limine -- Know your audience -- Judge's viewpoint -- Trial lawyer's viewpoint -- Appendix: Preparing witnesses for deposition -- Appendix: Legal writing tips